Problematika Hukum dan Ideologi Islam Radikal [Studi Bom Bunuh Diri Surabaya] - Abd. Halim; Abdul Mujib Adnan (Sultang Agung Islamic University, 2018)
Radicalism in Islam is part of a socio-religious phenomenon that cannot be separated from many aspects. Besides economic and political interests, Radicalism in Islam can also be seen from the legal and ideological aspects. The law forms ideology, and the culmination of it is extremist action, including terrorism. Suicide bombings in Surabaya (2018) are part of the chain of extremist action and terrorism. Understanding bombing cases like in Surabaya, is not enough to be seen from the outward aspects only but also the basic foundation for forming the awareness of the perpetrators. This paper uses the theory of social action from Pierre F. Bourdieu, to read how values are internalized into oneself and then externalized into suicides, as well as to map the domains and capital owned. This socio-political research proves that acts of terror, including suicide bombings, are actualizations of complex ideological symbolism. Therefore, terrorism is part of space competition, both the space for religious interpretation, the physical space for action, and the human space for image and evaluation. The justification of terrorism is supported by a set of legal and theological arguments, as well as terrorism action also have legal and theological tools